Profile of Mathematical Problem-Solving Ability in Students with Attention Deficit Hyperactivity Disorder (ADHD) Based on Their Emotional Intelligence - Ferry Romadhona; Kamid Kamid; Rohati Rohati (MASI Mandiri Edukasi, 2025)
Mathematical problem-solving is a critical skill, particularly for students with Attention Deficit Hyperactivity Disorder (ADHD), whose abilities in this area are influenced by emotional intelligence. This study aims to analyze the mathematical problem-solving skills of ADHD students with their emotional intelligence levels. A qualitative case study approach was applied, involving three ADHD students with varying levels of emotional intelligence—high, moderate, and low. The results revealed that students with high and moderate emotional intelligence could meet all key indicators of mathematical problem-solving, including understanding the problem, planning solutions, implementing strategies, and evaluating results. However, students with moderate emotional intelligence exhibited less structured strategies and checking procedures. In contrast, ADHD students with low emotional intelligence struggled at all stages, particularly in understanding the problem and planning solutions, and were unable to perform double-checking. These findings highlight the significant role of emotional intelligence in enhancing mathematical problem-solving abilities in ADHD students. The higher the emotional intelligence, the better the students can solve mathematical problems. These results emphasize the need for tailored educational strategies integrating emotional intelligence development to support ADHD students' academic success.